2012
DOI: 10.4236/ojsst.2012.23014
|View full text |Cite
|
Sign up to set email alerts
|

Injuries of Three Health Care Districts Employees in Finland

Abstract: Occupational injuries in hospitals have two-fold effects, decreasing both safety employees and the level of patient care. The aim of this study is to examine occupational injuries in Finnish hospitals. Three health care districts reported injuries and violent acts and the number of their employees over a period of three years: 2006-2008. Every eighth hospital worker was involved in an occupational injury each year, which is more than among the general working population. In addition, every twentieth hospital e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Nurses as frontline caregivers are at higher risk for NSI compared to other healthcare professionals. Salminen and Parantainen () indicated that NSI were responsible for more than 25% of the total occupational injuries in Finland, and that 54% of NSI occurred among nurses while 13% of NSI occurred among physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses as frontline caregivers are at higher risk for NSI compared to other healthcare professionals. Salminen and Parantainen () indicated that NSI were responsible for more than 25% of the total occupational injuries in Finland, and that 54% of NSI occurred among nurses while 13% of NSI occurred among physicians.…”
Section: Discussionmentioning
confidence: 99%
“…During dental practice, sharp devices and equipments such as needles, scalpels, root canal reamers, stitch cutters, glass ampoules, sharp instruments and broken crockeries and glasses are used and accidental injury may occur during the time of use or disposal. A recent study done on needle stick injuries have shown that these injuries leads to one fourth of the occupational injuries [1]. Dental staff working in clinics, may be exposed to blood-borne viruses (BBV) carried in blood, oral fl uids and tissues.…”
Section: Introductionmentioning
confidence: 99%